Modeling of bud break of Scots pine in northern Finland in 1908–2014 - Salminen, Hannu; Jalkanen, Risto (Frontiers in Plant Science, 2015)
Bud break and height-growth of Scots pine (Pinus sylvestris L.) in the northern boreal zone in Lapland, Finland, was followed through the entire growing seasons in the periods 2001–2003 and 2008–2010 in sapling stands in two different locations in northern Finland set some 250 km apart along a latitudinal transect. Field measurements continued at the southern site also in 2011–2013. Air temperature was recorded hourly at the sites. A simple optimization algorithm (GA) was used to adjust parameters of the models predicting the timing of bud break of Scots pine in order to minimize the difference between observed and predicted dates. The models giving the best performance and century-long daily temperatures were used to reconstruct bud-break time series. The temperature observations were recorded for the period 1908–2014 in Sodankylä, which is located in-between the sapling stands in the north–south direction and for the period 1877–2014 in Karasjok, which is in Norway about 145 km north–west from the northernmost stand of this study. On average buds began to extend in the beginning of May in the southernmost stand and in mid-May in the northernmost stands, and the variation between years was in the range of 3 weeks. A simple day-length-triggered (fixed date) model predicted most accurately the date of bud break; root mean square error (RMSE) was 2 and 4 days in the northern and southern site, respectively. The reconstructed bud-break series indicated that based on temperature observations from Sodankylä, growth onset of Scots pine has clearly advanced since the 1960s, though it currently matches that of the early 1920s and early 1950s. The temperature record from Karasjok indicated a similar variation, though there was a weak linear trend advancing bud break by about 3–4 days over a 100-year period.